Non-labile phosphorus acquisition by Brachiaria - Merlin, Alexandre [UNESP]; Rosolem, Ciro Antonio [UNESP]; He, ZhenLi (Taylor & Francis Inc, 2016)
Brachiaria are tolerant to low phosphorus (P) soils and may enhance P soil availability. The identification of mechanisms driving this effect is important. Our objective was to determine responses of palisade grass and ruzigrass to mineral oxide-bound P. Palisade grass (Brachiaria brizantha) and ruzigrass (Brachiaria ruziziensis) were grown in nutrient solution (NS), where P was supplied as goethite and amorphous aluminum-oxide (Al-oxide). Only half of each pot received P. Dry matter yields of Brachiaria species having oxide-P as the sole P source were similar to those grown with water-soluble P. Inorganic P was found in the NS after 7 days, and organic P at 14 days after plant emergence. The presence of dissolved organic carbon (DOC) indicates an intense and quick response of the root system to the treatments. Results indicate enzyme and/or organic acids (OAs) root exudation as a strategy of these plants to access soil sparingly soluble P forms.
Keywords: Phosphorus; rhizosphere; Brachiaria